Synthesis and Characterization of Ag@g−C3N4 and Its Photocatalytic Evolution in Visible Light Driven Synthesis Of Ynone. Issue 2 (28th November 2019) - Patel, Sunil B.; Vasava, Dilip V.
Abstract: The primary aim of this work is to synthesize photocatalyst to promote the synthesis of ynones. In this context, we synthesized AgNPs@g−C3 N4 nanocomposite. The nanocomposite was characterized by using SEM, HR‐TEM, XRD, EDS, ICP‐AES, UV‐Vis DRS, XPS, PL and FT‐IR. From the results of characterization, it was transpired that the AgNPs anchored firmly on the carbon nitride sheet and the size of nanoparticles ranges between 2–6 nm. We utilized the photoactive nanocomposite for the synthesis of various substituted ynones under visible light irradiation. Excellent yields were generated for the various substituted ynones (74–84 %). Furthermore, we study the gram scale synthesis and achieved yield up to 78 %. Recyclability of the nanocomposite was also studied and found that the material was recyclable up to 4 times without any significant loss in its activity. We have used 80 W tungsten bulb (λ>420 nm) as the light source and GVL (gamma Valero lactone) as the solvent which proves the process much greener as compared to the conventional methods. Abstract : Greener solvents : The authors have developed silver nanocomposite mediated synthesis of various substituted ynones in the presence of visible light. GVL was utilized as a greener solvent for the reaction. The use of 80 W tungsten bulb as a visible light source and heterogeneous catalyst makes the process sustainable.